1987
DOI: 10.1128/aac.31.8.1225
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of antiviral compounds on respiratory syncytial virus replication in vitro

Abstract: We examined the inhibitory effect of 20 antiviral compounds, including ribavirin, on the replication of respiratory syncytial virus in HeLa and HEp-2 cell cultures. Of the compounds studied, pyrazofurin and 3-deazaguanine emerged as more potent inhibitors of respiratory syncytial virus than ribavirin. Based on their inhibitory effect on the cytopathogenicity of respiratory syncytial virus in HeLa cells, the average 50% effective dose of pyrazofurin and 3-deazaguanine for eight strains was 0.07 and 1.65 ,ug/ml,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…The origins of the viruses and preparations of the virus stocks have been reported previously (8,9,15). Subtypes, strains, abbreviations, and passage histories of the viruses were as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The origins of the viruses and preparations of the virus stocks have been reported previously (8,9,15). Subtypes, strains, abbreviations, and passage histories of the viruses were as follows.…”
Section: Methodsmentioning
confidence: 99%
“…For the other viruses, confluent (MOCK, HeLa, Vero or E 6SM) cell cultures in 96-well microtitre trays were inoculated with virus at 100 CCID so (or with 100 plaque forming units of HCMV) per well in the presence of various concentrations of the test compounds. The cell cultures were further incubated at 35°C (for influenza A or B virus, RSV or parainfluenza type 3) or 37°C (for HSV-1, HSV-1 TK-, HSV-2 or HCMV), and virus-induced cytopathicity was monitored microscopically, as described previously (De Clercq et el., 1980;De Clercq, 1985;Kawana et al, 1987;Shigeta et al, 1988;Neyts et al, 1990). The concentration required to reduce virus-induced cytopathicity by 50% was estimated as the 50% inhibitory concentration (IC so ).…”
Section: Antiviral Activity Assaysmentioning
confidence: 99%
“…The virus stocks were prepared as described previously : influenza A virus (strain Ishikawa/7/82(H 3N2 »and influenza B virus (strain Singapore/222/79) (Shigeta et aI., 1988); RSV (strain Long) (Kawana et al, 1987); parainfluenza virus type 3 (strain VR-93) (De Clercq, 1985); HSV-1 (strain KOS), HSV-2 (strain G) and HSV-1 TK-(strain Field C/37/101) (De Clercq et al, 1980); HCMV (strain Davis) (Snoeck et al, 1988); HIV-1 (strain HTLV-lIls1LAI) and HIV-2 (strain LAV-2 ROD) (Pauwels et al, 1988). HIV-1 and HIV-2 were prepared from the culture supernatants of HIV-1-or HIV-2-infected cell lines (HUT-78/HTLV-IIIB and MT4/LAV-2 ROD, respectively).…”
Section: Virusesmentioning
confidence: 99%
“…Our study, to the best of our knowledge, is the first to demonstrate the antiretroviral activity of formycin A. Many previous studies identified the activity of 3-deazauridine against riboviruses (20)(21)(22)(23)(24)(25)(26) and retroviruses (23,27). Interestingly, 3-deazauridine was previously observed to potentiate the anti-HIV-1 activity of 3TC and dideoxycytosine (28).…”
Section: Discussionmentioning
confidence: 86%